The effectiveness of transitional care interventions for adult people with heart failure on patient-centered health outcomes: A systematic review and meta-analysis including dose-response relationship. (May 2021) - Li, Yuan; Fu, Mei R.; Fang, Jinbo; Zheng, Hong; Luo, Biru
Abstract: Background: Transitional care interventions that bridge the care gap from hospital to home have proven to be effective in lessening the burden of healthcare systems by reducing hospital readmissions. Yet, the effects of transitional care interventions on patient-centered health outcomes of mortality, quality of life, and emotional distress remains unclear. Objectives: To evaluate the effectiveness and dose-response of transitional care interventions on patient-centered health outcomes of mortality, quality of life, and emotional distress among individuals with heart failure and to identify the trial-level characteristics potentially affecting the overall effectiveness. Design: Systematic review with random-effects meta-analysis, meta-regression, and dose-response analysis of randomized controlled trials comparing transitional care interventions with usual care in adult people hospitalized with heart failure. Data sources: Electronic databases including MEDLINE, Embase, Cochrane Library, and CINAHL were systematically searched from January 1, 2000 to June 31, 2020. Review methods: Authors independently reviewed the retrieved articles based on inclusion and exclusion criteria, extracted data, and assessed risk of bias using the Cochrane risk-of-bias tool version 2.0. We pooled data from each study using random-effects meta-analysis and performed meta-regression to explore the impact of pre-specified trial-level factors. Dose-response meta-analysis was conducted to examine the relationship between the intensity (i.e., frequency and duration of interventions) and complexity (i.e., number of intervention components) of transitional care interventions and the treatment effects. Results: Data were synthesized from 42 trials covering a total of 10, 784 people with heart failure. Comparing to usual care, transitional care interventions achieved pooled evidence of a mean 18% risk reduction on mortality (0.82, 95% CI 0.71 to 0.95, P  = 0.009) and better improvement in quality of life (-4.37, 95% CI -7.20 to -1.54, P  = 0.002). There were insufficient data to determine with certainty the effects on anxiety and depression. Meta-regression showed greater efficacy in trials that delivered the intervention by a multidisciplinary team. Dose-response analyses demonstrated that mortality and quality of life were improved with increased intensity and complexity of the transitional care interventions. Conclusions: Transitional care interventions were effective in reducing mortality and improving quality of life for adult people with heart failure. The effects on emotional distress were inconclusive due to insufficient data, highlighting the need for further research. Registration number: CRD42019132732